Integrated thermoelectric model for on-board aircraft generators. Issue 21 (2016) - Amarantidis, G.A.; Dixon, R.; Hubbard, P.D.; Harrington, I.
Abstract: Electronic systems are becoming the predominant method for flight critical systems and have substituted their pneumatic or hydraulic counterparts, increasing the need for constant and uninterrupted supply of power. One of the main limitations is overheating in generators due to an increased demand of current. Overheat in the generator windings can lead to insulation degradation and hence to catastrophic failure. Therefore, understanding and monitoring heat flow through the generator is of utmost importance. Previous studies have viewed the electrical and thermal circuits as separate arrangements with little interaction between the two. This paper attempts to provide a systemic thermo-electric view of the generator and offer a method for interfacing the thermal and electrical circuits by the use of loss calculation. The long term goal of this project is to provide a means for model based health assessment and intelligent power management for on-board aircraft generator systems, while having limited information on the system itself.